A turizmus szerepe Mórahalom fejlődésében - Martyin, Zita; Boros, Lajos (Közép-Európai Közlemények, 2012)
Nowadays tourism can be a key element of urban and regional competitiveness. It could boost the development of cities and regions through enhancing incomes and employment. Furthermore, tourism also helps to raise the quality of life. Our aim is to present that with adequate planning and developments a less-known town can become a tourist attraction, too. Of course, the planning and development processes must take into consideration the local characteristics. The paper presents the case of Mórahalom, which is a small town in Southern Hungary. Mórahalom one of the most dynamic towns in its region: once a farm center became a tourist attraction with rapidly growing number of visitors. Few decades ago agriculture was the main economic sector in the area but after massive investments into Spa industry. These investments accelerated the development of Mórahalom and quickly restructured its local economy and society, too. First, local people have started to offer lodgments for tourist then a guesthouse and a four star hotel have opened in the town. Our paper is based on the content analysis of local media and development documents, survey and statistical analysis of the database of the guesthouse. According to our results the visitors are pleased with the Spa and the services offered in Mórahalom. Most of them plan to return in the future.